Analysis of Types, Intensity, Methods and Effects of Process Innovations - Pavla Macurová; Jindra Peterková; Katarzyna Czerná (Kvalita Inovácia Prosperita, 2019)
Purpose: The purpose is to provide knowledge about the intensity and types of process innovation in the business sphere, as well as the representation of entities involved in creating innovation, and about the effects of process  innovation.